A kinetic study on accumulation and depuration of hexavalent chromium in crucian carp (Carassius auratus) reveals the potential health risk of fish head consumption. (December 2021) - Yin, Jiaojiao; Zhang, Feng; Wang, Li; Li, Sai; Huang, Taotao; Zhang, Xuezhen
Abstract: In this study, crucian carp ( Carassius auratus ) was exposed to graded levels of waterborne Cr 6+ (0, 0.1, 1 and 10 mg/L) for 28 days and subsequently transferred to clean water for 20 days. Fish tissues were collected every 4 days. The Cr 6+ levels in tissues were determined and the potential health risks from consuming fish muscle and fish head were assessed. The results indicated that the Cr 6+ contents in the head were always higher than those in muscle and that 10 mg/L Cr 6+ treatment conferred risk in fish head consumption throughout the entire experimental period. A further kinetic study on the accumulation and depuration of Cr 6+ in tissues indicated that compared to muscle, the higher Cr 6+ content in fish head was attributed to the greater uptake rate (k1 ) and kinetic bioconcentration factor (BCFk ), although the k1 and BCFk values in the muscle and head were lower than those in the liver, kidney, intestines and gills. The maximum Cr 6+ concentrations in tissues at theoretical equilibrium (Cmax ) ranged from 0.55 mg/kg in muscle to 112 mg/kg in intestines with exposure to 10 mg/L Cr 6+ . Moreover, the results of the distributions and transitions of Cr 6+ in fish tissues demonstrated that fish head and muscle were short-term storage organs while the kidney was a long-term storage organ for Cr 6+ . Overall, compare to muscle, fish head has a higher capacity for Cr 6+ accumulation, which poses a higher potential health risk to humans, especially to children, once the fish is contaminated by Cr 6+ . Highlights: The kinetics of Cr 6+  in fish tissues were studied using a two-compartment model. Fish head has a higher uptake rate for Cr 6+ than that in fish muscle. The relative burdens of Cr 6+ in fish tissues were firstly reported. Fish head and muscle could be short-term storage organs of Cr 6+ . Kidney could be a long-term storage organ of Cr 6+ .